2017
DOI: 10.3389/fncel.2017.00106
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Immune Infiltrates to Ototoxicity and Cochlear Hair Cell Loss

Abstract: Cells of the immune system have been shown to infiltrate the cochlea after acoustic trauma or ototoxic drug treatment; however, the contribution of the immune system to hair cell loss in the inner ear is incompletely understood. Most studies have concentrated on the immediate innate response to hair cell damage using CD45 as a broad marker for all immune cells. More recent studies have used RNA sequencing, GeneChip arrays and quantitative PCR to analyze gene expression in the entire cochlea after auditory trau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(104 citation statements)
references
References 54 publications
4
100
0
Order By: Relevance
“…The nature of the immune cells infiltrating the cochlea has been discussed in a recent review (Wood and Zuo, 2017), and will not be addressed here. The infiltrating cells transform into activated macrophages and express pro-inflammatory proteins (Yang et al, 2015).…”
Section: The Inflammatory Response and Its Resolutionmentioning
confidence: 99%
“…The nature of the immune cells infiltrating the cochlea has been discussed in a recent review (Wood and Zuo, 2017), and will not be addressed here. The infiltrating cells transform into activated macrophages and express pro-inflammatory proteins (Yang et al, 2015).…”
Section: The Inflammatory Response and Its Resolutionmentioning
confidence: 99%
“…Their properties and functions are mainly determined by local environmental factors, which allows them to adapt highly to the needs of their anatomical niche. Studies have shown that after noise exposure, the distribution, phenotype, and the number of cochlear macrophages have significantly changed, and the local environmental factors that shape macrophage differentiation and behavior are also drastically altered, which supports the concept that macrophages play a vital role in cochlear response to acoustic injury [3,5]. However, the exact role of these immune cells in the cochlea after noise exposure remains unknown.…”
Section: Introductionmentioning
confidence: 73%
“…However, the cellular and molecular mechanisms underlying NIHL have not been fully clarified, therefore, clinically NIHL lacks effective therapeutic methods. Recently, inflammation and immune response have been increasingly recognized as important pathophysiological mechanisms underlying irreparable or reparable damage to hair cells and neurons after acoustic injury [1][2][3]. As the major professional immune cells in the cochlea, macrophages contribute to the inflammation, repair, and homeostasis, playing a critical role in local cochlear immunity [4].…”
Section: Introductionmentioning
confidence: 99%
“…A hair cell with necroptotic response thus would only make sense if the inner ear was not “immune privileged” as historically assumed but was capable of mounting a significant immunological response. In fact, more recent studies suggest that the resolution of ototoxic insults is aided by immune cells infiltrating into the inner ear (Kaur, 2015; Kaur et al, 2015, 2018; Francis and Cunningham, 2017; Mizushima et al, 2017; Wood and Zuo, 2017; Barald et al, 2018; Liu et al, 2018). Such immune activity, beneficial under normal circumstances, might become counterproductive when ototoxins overwhelm the system, creating a massive, detrimental immune response.…”
Section: Discussionmentioning
confidence: 99%